Knowledge, attitudes, and practices toward onchocerciasis among local population in Bioko Island, Equatorial Guinea - Alonso, LauraMoya; Ortiz, ZaidaHerrador; Garcia, Belén; Nguema, Rufino; Nguema, Justino; Ncogo, Policarpo; Gárate, Teresa; González-Escalada, Alba; Benito, Agustín; Azcarraga, PilarAparicio (Annals of tropical medicine and public health, 2017)
Introduction: Since 1998, the African program for onchocerciasis control has been working with ultimate goal of reducing the public health impact associated with onchocerciasis in Equatorial Guinea. Although dedicated community engagement is crucial for the success of this program, there is no information on the levels of community's knowledge, attitude, and practice (KAP) toward onchocerciasis in this country. Methods: A cross-sectional study was carried out in Bioko Island from mid-January to mid-February 2014. Sampling was carried out by multistage cluster survey. Sociodemographic characteristics, KAP, and stigma-related questions were collected through a pretested questionnaire. A bivariate analysis was performed and results were adjusted by sex and age using logistic regression. Results: A total of 140 housekeepers or head of households agreed to participate. Around 54% of the interviewees had heard about the disease, of which more than one-third identified the disease as filariasis (28/68, 41.2%). Overall, 19.3% respondents highlighted the bite of a blackfly as the main mode of transmission. From those who had a familiar affected by onchocerciasis in the past, 21 out of 32 (65.6%) pointed ivermectin as the preferred treatment and 43.8% pointed out the health center as the first choice place to seek for treatment. About 67.1% of individuals believed that having onchocerciasis would not cause any contact avoidance with other members in the community. Conclusions: People's practices toward onchocerciasis tend to be better than disease knowledge in Bioko Island. Increasing awareness through community-based campaigns and educational activities is encouraged in the current onchocerciasis preelimination stage at Bioko Island.